APOE4 and chronic health risk factors are associated with sex-specific preclinical Alzheimer’s disease neuroimaging biomarkers - Genna M. Losinski; Mickeal N. Key; Eric D. Vidoni; Jonathan Clutton; Jill K. Morris; Jeffrey M. Burns; Amber Watts; Amber Watts (Frontiers in Global Women's Health)
IntroductionTwo thirds of Alzheimer's disease (AD) patients are female. Genetic and chronic health risk factors for AD affect females more negatively compared to males.ObjectiveThis multimodal neuroimaging study aimed to examine sex differences in cognitively unimpaired older adults on: (1) amyloid-β via 18F-AV-45 Florbetapir PET imaging, (2) neurodegeneration via T1 weighted MRI volumetrics, (3) cerebral blood flow via ASL-MRI. We identified AD risk factors including genetic (APOE genotype status) and health markers (fasting glucose, mean arterial pressure, waist-to-hip ratio, and android and gynoid body fat) associated with neuroimaging outcomes for which we observed sex differences.MethodsParticipants were sedentary, amyloid-β positive older adults (N = 112, ages 65–87 years) without evidence of cognitive impairment (CDR = 0).ResultsMultivariate analysis of covariance models adjusted for intracranial volume, age, and years of education demonstrated lower volume [F (7, 102) = 2.67, p = 0.014] and higher blood flow F (6, 102) = 4.25, p ≤ 0.001) among females compared to males in regions of interest connected to AD pathology and the estrogen receptor network. We did not observe sex differences in amyloid-β levels. Higher than optimal waist to hip ratio was most strongly associated with lower volume among female participants.DiscussionFindings suggest genetic and chronic health risk factors are associated with sex-specific AD neuroimaging biomarkers. Underlying sex-specific biological pathways may explain these findings. Our results highlight the importance of considering sex differences in neuroimaging studies and when developing effective interventions for AD prevention and risk reduction.